2016
DOI: 10.1111/1753-6405.12522
|View full text |Cite
|
Sign up to set email alerts
|

Positive community responses to an arts–health program designed to tackle diabetes and kidney disease in remote Aboriginal communities in Australia: a qualitative study

Abstract: Objective: The Western Desert Kidney Health Project (WDKHP) is an innovative clinical screening, arts–health and community development program, staffed by Aboriginal health workers. The WDKHP is aimed at prevention and early detection, improving the chance of better management of kidney disease among people in 10 predominantly Aboriginal communities in rural Western Australia. This paper aimed to understand community responses to the WDKHP in three of these communities. Methods: Interviews were undertaken with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Of the two mobile clinics evaluated using mixed methods (e.g. including qualitative methods of data collection such as interviews and focus group sessions), one evaluation did not provide qualitative data [ 63 ], whereas the other provided rich qualitative findings with evidence of engaging with the perspectives and voices of Indigenous people [ 65 , 66 ]. Evaluations were heterogeneous in terms of evaluation methods and outcomes, making it difficult to compare findings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the two mobile clinics evaluated using mixed methods (e.g. including qualitative methods of data collection such as interviews and focus group sessions), one evaluation did not provide qualitative data [ 63 ], whereas the other provided rich qualitative findings with evidence of engaging with the perspectives and voices of Indigenous people [ 65 , 66 ]. Evaluations were heterogeneous in terms of evaluation methods and outcomes, making it difficult to compare findings.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple challenges including planning and coordination of outreach clinics, recruitment of staff and staff turnover, van procurement, launch and ongoing promotion of clinical service, ordering of equipment and logistical organisation, development of a database for electronic record keeping and negotiating fees to minimize costs to clients. National Partnership Agreement for ‘Closing the Gap’ in Indigenous Health Outcomes Western Desert Kidney Health mobile bus All Aboriginal and Torres Strait Islander people Early detection of disease, chronic disease management and health promotion Implemented and delivered in partnership with Aboriginal organisations (1) Qualitative interviews [ 65 ] (2) Community based participatory research project with annual cross sectional surveys over 3 years [ 66 ] (1) Aboriginal people living in remote communities receiving service (n = 26) (2) Aboriginal people from 10 locations (1) Found to be highly acceptable and effective means of disseminating the importance of prevention, early detection and management of diabetes and kidney disease (2) Multiple outcomes including high participation rate of Aboriginal people (79%), higher than predicated rates of diabetes, hypertension, hematuria and ACR and Aboriginal women found to be the highest risk group BHP Billiton Nickel West, University Western Australia, University of Notre Dame, Bega Garnbirringu Health Services, Goldfields Esperance GP Network and Wongutha Bimi Aboriginal Corporation Budja Budja Aboriginal Cooperative All Aboriginal and Torres Strait Islander people Primary health care services including audiology, optometry, general health checks and health promotion and education Implemented and delivered None to report None to report None to report Deakin University School of Medicine, Department of Prime Minister and Cabinet (Indigenous Affairs) and Budja Budja Aboriginal Coopertaive Queensland Aboriginal and Islander Health Council (QAIHC) mobile health clinic Aboriginal and Torres Strait Islander people Primary health care services Not reported None to report None to report None to report Queensland Gas Company (QGC) Goondir Health Services Mobile Medical Clinic Aboriginal and Torres Strait Islander people, including school-aged children Primary health care including disease prevention and chronic disease management, men’s and women’s health and health checks in schools Delivered by an Aboriginal Community Controlled Health Organisation Descriptive statistics of services delivered [ 69 ] Clinic data Multiple outcomes including 187% increase in number of patients over 4 years. Queensland Health, Broncos and Goondir He...…”
Section: Resultsmentioning
confidence: 99%
“…Inadequate access to early screening and prevention has been noted in low SES populations in the United States 22 ; ethnic minority populations in the United States 23 - 25 ; and in Indigenous populations in Canada and Australia. 5 , 9 , 26 - 28 These populations also experience disparities in access to all renal replacement therapies, as do rural/remote populations, undocumented immigrants, the unemployed, and substance misusers. It has been shown that disadvantaged populations experience reduced access to and worse outcomes from dialysis treatments.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, regional programs seek to improve the quality of healthcare afforded to ATSIs. The Greater Northern Australian Regional Training Network, for example, provides supplemental training for healthcare workers engaging ATSI populations, while the Western Desert Kidney Project has developed an innovative diabetes screening program, incorporating a community arts program to disseminate "culturally appropriate health messages" as well as community development officer to work on "structural issues" such as advocacy and grant applications [50,51]. Beyond generalists, otolaryngology programs such as the Ear Bus Foundation and the Western Australian Coutry Health Service's Kimberly ENT Outreach Clinic offer services targeted to OM and ear related disorders [52,53].…”
Section: Programs To Combat Inequalitymentioning
confidence: 99%